(3QSGdI aj CMcGe GdMjV hGdGSJMGVI Ydi ePgH CHj MfjaIs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; hGdMeOdI jbhd GdYHO GdPdjd gPg gj GdUhQI GdCQHYjI eY GdNeSI hVYgG GdeUfa dHjGf GdePGgH hGdCbhGH GdSJI aj HjGf MGd MjV GdeQCI GdMGFV GdeHJOGFjI (B( (3cPG (B) (3ePgH CHj jhSa hgh bhd GdEeGe CHj MfjaIs
(3BNQgG (B:s
(3hcPG aj QhGjI GHf GdeHGQc EPG QCJ jheG Ch jhejf OeG hKeGfjI WgQG hjheG Ch jhejf OeG aGdCjGe GdOehjI cdgG GSJMGVI hbS Ydjg SGFQ GdePGgH aJOHQ aEf gPG HMQ Yejb dG jfJgj JUhjQGJg dG SjeG CMhGd GdeYJGOI hGdeJfbdI hGdeJMjQI HMjK jJMjQ ajgG ChdhG GdCMdGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3Gdabg GdMfHdjs